False Memory in Alzheimer’s Disease - Mohamad El Haj; Fabienne Colombel; Dimitrios Kapogiannis; Karim Gallouj (Behavioural Neurology)
Patients with Alzheimer’s Disease (AD) not only are suffering from amnesia but also are prone to memory distortions, such as experiencing detailed and vivid recollections of episodic events that have never been encountered (i.e., false memories). To describe and explain these distortions, we offer a review to synthesize current knowledge on false memory in AD into a framework allowing for better understanding of the taxonomy and phenomenology of false memories and of the cognitive mechanisms that may underlie false memory formation in AD. According to this review, certain phenomenological characteristics of memories (e.g., high emotional load, high vividness, or high familiarity) result in misattributions in AD. More specifically, this review proposes that generalized decline in cognitive control and inhibition in AD may result in difficulties in suppressing irrelevant information during memory monitoring, especially when irrelevant (i.e., false) information is characterized by high emotion, vividness, or familiarity. This review also proposes that binding deficits in AD decrease the ability to retrieve relevant contextual details, leading to source monitoring errors and false memories. In short, this review depicts how phenomenological characteristics of memories and failures of monitoring during retrieval contribute to the occurrence of false memory in AD.